Physical fitness of boys with overweight and obesity living in the eastern provinces of Poland - Saczuk, Jerzy; Olszewska, Dorota; Wasiluk, Agnieszka; Olszewski, Jarosław (Polish Journal of Public Health, 2011)
Introduction. In many European countries and worldwide the civic development contributes to changes in the lifestyle of entire societies. Although obesity is claimed to be a problem of highly-developed countries, it is also becoming noticeable in regions with a lower rate of development. Aim. The study was aimed at determining the level of physical fitness of boys with overweight and obesity being at different stages of the biological development. Material and methods. Out of the extensive material of the study, which took place in the years 1986, 1996 and 2006, covering the physical development and physical fitness of children and adolescents 8236 boys from the following Provinces: Podlaskie, Lubelskie and Podkarpackie, which were surveyed in 2006, were selected for the study. Trials of physical fitness were conducted following guidelines of the International Test of Physical Fitness. Next, the experimental material was divided into categories taking into account stages of the biological development, thus classifying the boys into three groups: pre-pubescence, pubescence and post-pubescence. Based on body height and body mass measurements, BMI values were calculated for each subject. In the reported study, the boys were classified to a group of overweight or obesity based on recommendations of the International Obesity Task Force, taking into account boundary values elaborated by Cole et al 2000. Results. The analysis of the experimental material indicates that, as compared to the average data, the obese boys achieved better results only in the hand grip test and their peers with overweight additionally in locomotive speed and agility. In the case of the other motor capabilities, the evaluated boys achieved worse results as compared to the reference group. Similar tendencies were observed in all stages of development, and differences between them occurred only in the level of results. Conclusion. The results obtained in this study allow us to conclude that boys who are overweight and obese have different physical fitness levels.